2023
DOI: 10.4236/ijmnta.2023.123006
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Decomposition Shooting Method for Solving Third-Order Boundary Value Problems

Nawal Al-Zaid,
Kholoud Alzahrani,
Huda Bakodah
et al.

Abstract: The present paper proposes a mathematical method to numerically treat a class of third-order linear Boundary Value Problems (BVPs). This method is based on the combination of the Adomian Decomposition Method (ADM) and, the modified shooting method. A complete derivation of the proposed method has been provided, in addition to its numerical implementation and, validation via the utilization of the Runge-Kutta method and, other existing methods. The method has been applied to diverse test problems and turned out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The shooting method [4] coupled with the ADM is an iterative method that has been widely utilized to solve various classes of BVPs [7,8,[20][21][22][23]. However, the iterative shooting method procedures for solving both cases of linear and nonlinear BVPs remain the same [9], except for the fact that the solution of the nonlinear model cannot be represented as a linear combination of the solutions of two IVPs. As such, the solution of the governing BVP (1)-( 2) is approximated by those of the IVPs, with t as a parameter.…”
Section: Edsm For Third-order Nonlinear Bvpsmentioning
confidence: 99%
See 2 more Smart Citations
“…The shooting method [4] coupled with the ADM is an iterative method that has been widely utilized to solve various classes of BVPs [7,8,[20][21][22][23]. However, the iterative shooting method procedures for solving both cases of linear and nonlinear BVPs remain the same [9], except for the fact that the solution of the nonlinear model cannot be represented as a linear combination of the solutions of two IVPs. As such, the solution of the governing BVP (1)-( 2) is approximated by those of the IVPs, with t as a parameter.…”
Section: Edsm For Third-order Nonlinear Bvpsmentioning
confidence: 99%
“…Through their results, they concluded that the shooting method seems to be sufficiently convergent for the system, and the shooting method is preferable to obtain numerical solutions where other methods seem to be laborious in mathematical treatment. Subsequently, Attili and Syam [8] proposed a combination of the Adomian decomposition method (ADM) and the shooting method to numerically examine second-order linear and nonlinear BVPs using a special integration operator; the same method was equally extended to third-order linear BVPs by Alzahrani et al [9]. Additionally, we also cite [10][11][12][13][14][15][16][17][18][19] and the references therein for some relevant considerations through the ADM, and also refer the reader(s) to [20][21][22][23] for certain deliberations on the shooting approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation